Integrated multi-omics reveals GABARAP-mediated mitophagy and pyruvate metabolism as key drivers of osteosarcoma progression - Han, Xiuxin; Li, Yiqin; Liu, Yongheng; Wang, Feng; Li, Tingfang; Zhang, Qingchen; Wang, Guowen; Feng, Jinyan (Frontiers in Immunology, 2025)
BackgroundOsteosarcoma is a highly aggressive bone malignancy characterized by frequent metastasis and therapy resistance. Although mitophagy and pyruvate metabolism are increasingly recognized as critical metabolic regulators, their interaction in osteosarcoma remains poorly understood. The autophagy-related protein GABARAP, central to mitochondrial quality control, has not been systematically evaluated in osteosarcoma.MethodsSingle-cell RNA sequencing (scRNA-seq) datasets (GSE162454, GSE237070) were analyzed to delineate cellular heterogeneity and malignant states, with prognostic clusters identified by Scissor and inferCNV. Tumor microenvironment (TME) composition and intercellular signaling were profiled using CellChat. Pathway enrichment and multi-omics integration across TARGET, GSE21257, and GSE32981 highlighted mitophagy-pyruvate coupling, which were further validated by spatial transcriptomics and in vitro functional assays.ResultsWe mapped the osteosarcoma ecosystem and identified two malignant subpopulations, Ost_1 and Cho_2 (Mal_Ost/Cho), exhibiting high genomic instability, stemness, and poor prognosis. The osteosarcoma TME displayed profound immune remodeling, characterized by infiltration of T/NK cells alongside enrichment of immunosuppressive Tregs and M2-polarized macrophages. Enhanced MIF-mediated signaling between Mal_Ost/Cho and T/NK compartments suggested a key mechanism of immune evasion. Both malignant subtypes demonstrated coordinated activation of mitophagy and pyruvate metabolism, sustaining metabolic adaptation and tumor progression. Multi-omics integration pinpointed GABARAP as a central hub regulating this mitophagy-metabolism axis, spatially enriched within metabolic hotspots and immunosuppressive niches. Functionally, GABARAP depletion disrupted mitophagy flux, mitochondrial integrity, and energy production, thereby impairing osteosarcoma cell proliferation and migration.ConclusionThese findings reveal that GABARAP links mitophagy-driven metabolic adaptation with immune evasion, representing a key regulator and potential therapeutic target in osteosarcoma.